Exploring methods to assess environmental health inequalities in health impact assessments of local interventions: a systematic review within the JA PreventNCD project - Properzi, Sara; Coa, Angela Andrea; Fiorilla, Claudio; Pasetto, Roberto (Frontiers in Public Health, 2025)
BackgroundHealth Impact Assessment (HIA) procedures can include the assessment of inequalities and inequities associated with the distribution of environmental health risks and benefits, aimed at attenuating the exacerbation of environmental health disparities. This systematic review, conducted as part of the Joint Action Prevent Non-Communicable Diseases initiative, explores methods for assessing health inequalities and equity within HIA frameworks, particularly in local projects affecting the distribution of environmental risks and benefits.MethodsAdhering to the PRISMA guidelines, a systematic review of the scientific literature was conducted using the MEDLINE/PubMed, Scopus, and Embase databases, searching until March 8, 2024. Furthermore, a grey literature analysis encompassed the Institutional Repository for Information Sharing (IRIS) of the World Health Organization, to identify guidelines and recommendations addressing equity considerations in HIAs. Studies were included based on predefined eligibility criteria if they explored issues related to inequalities, inequities, and vulnerabilities within the context of HIAs. Data extraction focused on methodologies that incorporated equity considerations within the HIA framework, particularly concerning local urban planning initiatives, transport infrastructure, and industrial settings.ResultsA total of 33 studies met the inclusion criteria. Among these, eight documents from the grey literature, identified as guidelines and guidance, underscored the importance of prioritizing equity to ensure that health impacts are addressed fairly across diverse population groups. The remaining 25 peer-reviewed studies employed a combination of quantitative and qualitative methodologies. Quantitative approaches, including exposure-response modeling and Geographic Information System (GIS) mapping, were utilized to evaluate spatial and demographic health disparities. Qualitative methods, such as focus groups, interviews, and participatory tools, provided insights into the lived experiences of vulnerable populations affected by local interventions. Studies addressing urban and transportation planning predominantly emphasized socioeconomic stratification, whereas those focused on industrial settings highlighted occupational hazards and community vulnerabilities.ConclusionThis review highlights the diverse and fragmented approaches used to address health inequalities and equity in HIA. It underscores the need for interdisciplinary and systematic methodologies that integrate quantitative and qualitative perspectives, ensuring equity remains a central consideration in policymaking and project implementation. Finally, it proposes a practical framework for integrating equity into HIA.